Co-producing transformative visions for Europe in 2100: A multi-scale approach to orientate transformations under climate change. (October 2022) - Hölscher, Katharina; Frantzeskaki, Niki; Jäger, Jill; Holman, Ian; Pedde, Simona
Abstract: Achieving sustainability and resilience transformations under climate change requires transformative and multi-scale visions to stimulate coherent thinking and action towards radically alternative futures. We present our approach to co-produce transformative visions contextualised in different regions across Europe, while exploring emergent 'pan-European' vision elements to guide transformative climate action across scales. We co-produced visions with stakeholders in four case studies: European, national (Scotland), transboundary river basin (Iberia) and two municipalities (Hungary). All visions share core aspirations for good living, justice and social and environmental wellbeing in Europe, while allowing contextualised interpretation to remain meaningful in view of context-specific needs, priorities, cultural perceptions and aspirations. The visions point to areas where deep transformations are required: in service provisioning from critical infrastructures like energy, food, health and education, and in lifestyles and governance. We discuss two key methodological considerations for the co-production of transformative visions across multiple scales. Firstly, the application of a systematic and comprehensive framework across all scales provided a guide to compare and ensure coherence between visions across multiple scales. Secondly, the creation of transformative spaces to co-produce the visions with stakeholders supported critical reflections and learning about the radical and multi-dimensional changes necessary in different regions in Europe. Highlights: Transformative visions can be important drivers of desirable societal change. Transformative visions need to be contextualised and coherent across scales. A systematic framework guides coherent envisioning across multiple scales. Transformative spaces gauge critical reflections, learning and empowerment. Pathways can translate visions into concrete actions to support implementation.